Tanburi Cemil Bey'in kemençe icrasının özellikleri - Başar Çelik, Binnaz (Sosyal Bilimler Enstitüsü, 1995)
During the period Tanburi Cemil Bey lived in İstanbul, this capital city of the Ottoman Empire was a rich assemblage of many different peoples, who migrated to İstanbul from the frontiers of the Empire embracing three continents. Tanburi Cemil Bey has tasted ine essence of the folk music and he could perfonn according to the authentic style and technique, as if he was a folk musician. Tanburi Cemil Bey's interest in the Western music is the other majör aspect of his art. He has read books on Western music and experimented with Western notes. He was raised in an environment of traditional "fasıl" music. But he managed to create at the beginning of mis century, a unique İstanbul music by melting in his own artistic character the conflicting effects of the different kinds of music performed m that era. Musical sentences \vhich are structured from totally new patterns, unheard until that time, as well as his music perfected on various instruments with great virtuosity are ali fruits of this creative period. it is not knovm clearly during which years he began to work for Turkish classical music. He arose from a familiar environment where music was beloved, During a meeting held with musicians his cousin introduced him to "Tanburi Ali Efendi" a compositor, since he recognized his ability of playing Tanbur Cemil Bey did not take lessons from Ali Efendi but leamed the primary details regarding the classical music of "fasıl" (concert) and the common elements thereof. He further learned Hamparsum notation as well as the notation of westerly music. During the, years- of his education, the main institurions teaching Turkish Classical Music were Enderun and the lodges of Mevlevi dervishes. during that age, the education of Turkish Classical Music had nearly lost its signifîcance in Interior of Music. On the other hand, Cemil Bey was neither from a Mevlevi family, nor he was a Mevlevi. Therefore, he had to prepare the aspects of his education through his own efforts. He has fundamentally altered the traditional fact of deviating realizarion of melodic lines by Tanbur that connected numerous phonation with öne impact of plectrum beneficing from the resonances arising from the deep body of tanbur instead of using the plectrum for separate notes each. Thus, he led to a motion based upon strong plectrum usage instead of the style slovving the IV perfonnance and developed a very new technique combining the plectrum impacts following each other, through an ewtraordinary elegance he reached on left hand. He was an artist able to play violoncello wim the bow of kemence for performing Turkish Classical Music with a chord that can reflect it. He was even apt to perfonn works having a fast moderation such as "köçekçe". it wes Cemil Bey too, who played "Yaylı Tanbur" as first. He played with violin and small violin bow, using them wim the same elegance and atended the concerts with those. Although it is unknown when he started playing the kemence, it is known that he concentrated on it more and more towards the end of his life. His first performances reflected Vasil's style. Later, he perfected Vasil's style, while he mastered the bow. Tanburi Cemil Bey regards as invaluable entertainments, his ovra "kemence" innovations like imitating human voices, the sheep, ör the flüte of the shepherds. However, meşe pieces are considered to be lyric, pastoral and descriptive pieces carrying virtuoso values. Tanburi Cemil Bey is the first Turkish musician who performed publicly. He tought music at the Darül Bedayi. his works are analyzed in two parts. Among his vvritten works, there is the unfinished dictionary and method for the "kemence", the "Kaamus-ı Musikiw. His "Rehber-i Musiki" is the first theory book which compares the traditional Turkish music with Western music. His composition except the introductory improvisations have been printed as complete works, twice. The first recording of Tanburi Cemil Bey were on resin cylinders. Later his music was recorded on one-sided records. Tanburi Cemil BeVs fame spread, with the spread of the phonograph and the gramophone, mroughout the Ottoman Empire, as well as to Iran, Morocco and the BaÜcans. A great majority of his recording belong to the Orfeon Record company of the Blumenthal Brothers, recorded between 1910 and 1914. Between 1914 and 1916, he played for a few Regent records. Most of his recordings are solo. Udi Nevres Bey, Udi Şevket Bey, Piyanist Cemal Bey, Neyzen Rıza Bey, Kanuni Ziyaeddin Efendi, talebesi Tanburi Kadı Fuat Efendi, Kemani Bülbül-i Salih and Udu Fethi Bey are V among the musicians who accompanied Tanburi Cemil Bey. He was in great harmony with the "hafız" s who accompanied him during his "teksim" s, Among these were Hafiz Osman, Hafiz Aşir, Hafiz Yaşar Okur, Hafiz Yakup and Hafiz Sabri. Tanburi Cemil Bey particularly preffered the accompany of Hafiz Osman. Tanburi Cemil Bey's work can be investigated from the viewpoint of three aspect; his "taksim" s (ünprovisations), his virtuosity and his composing. Tanburi Cemil Bey is regarded as the best "taksim" virtuoso of the traditional Turkish music ever known. His "taksim" s that we can hear from the records today are in fact evaluated as "improvised compositions". These "taksim's" which are played on different instruments and accords depending on their themes and whose ali musical sentences are unique, comply with the "zemin-teslim-meyan-teslim" stnıcture commonly practiced in the Turkish music. Tanburi Cemil Bey usually performed his "taksim"s in two parts. Sentences and the sub-sentences show an asymmetry among themselves. The periods of the divisions can be considered equal. The tails attached to the ends of the sentences can sometimes be viewed as the beginnings of the coming sentences. in the octave question-answer desingn, the question is usually longer than the answer. This clearly illustrates the asymmetric taste of Tanburi Cemil Bey's music. Tanburi Cemil Bey has utulized the notes as dictated by the "makam"s. According to the stnıcture of the piece, he altered teh characteristic notes of the common" makam"s, "hüzzam", "karcığar" and "saba", as well as the hicaz flavor of the "makams" "neva" and "çargah." it is a \videly-accepted fact that Tanburi Cemil Bey was more innovative and modern in comparison with his contemporaries, but was stili conservative as far as the "makam" s were concerned. in Tanburi Cemil Bey's "taksim"s, we hear rhythmic concentrations in fast passages, followed by sentences of calm style and interrupted playing. Octave question-answer sentences, short breaks between the sentences and sharp stops at the end of the sentences are sure signs of his style. Melodic promenades, triole's, 16th an 32 nd notes, staccato's, descending and ascending figures allowed him to perform his "taksim"s so vividly. VI The intricacies of the performed pieces of music are only revealed by the nuances. Tanburi Cemil Bey skilfully utilized the nuances that would fit specific parts of the "kemence". Since he usually played with closed tunes and positions, the tone differences between the strings are almost diminished. The "vibrato", which is one of the tone qualities, can only be heard during the very long notes. Accent is one of the most important factors for the rhythm. In Tanburi Cemil Bey's music, a accent syncope appears as a result of the accent that coincide with the strong and weak periods. The instrumental music Tanburi Cemil Bey performed for his records clearly reflects his style. He played the "peşrev"s, "saz semai"s and even songs in a new approach, with melodic and rhythmic colors that were not part of the original piece. This approach, which brings interpretation to the piece reflect the understanding which emphasises the difference between the written notes of a piece of music and its performance. One example to this is the difference between the script and the performance of the "Uşşak Peşrev" composed by Tanburi Büyük Osman Bey. Decorating the "teslim" part of any instrumental work with a different innovative change every time it is played, is another example of this attitude. Dividing long notes into shortes ones, using broderie notes, putting a simultaneous note above or below the melody, filling in between two main notes with ornamental notes, simplifying a note group, making attachments to the front or end of a note group, substitution of an equivalent note for a rest, alteration of the rhythmic structure, or playing the piece one octave lower, are all characteristics of Tanburi Cemil -Bey's performance. He has fundamentally altered the traditional fact of deviating realization of melodic lines by Kemence that bow can be pulled during fhestrong duration, in the weak, term, it can be pushed. The passages consisting of long notations during the improvisations of Cemil Bey can technically played on one bow but the long the time of bow impact lasts, less sorority is obtained. Eventually those have been played on two bows with pulling and pushing. İn his performances we often realize Piccicato and Straccato bow techniques. vn In the classical Turkish music, a concept of virtuosity as conceived in the classical Western music cannot be observed. The things we know about the performance styles and education methodology, as well as the musical work we have inherited all indicate that such a virtuosity concept was absent in the Turkish music until the beginning of this century. What is meant by virtuosity is in fact not merely the concrete skill criteria relevant to the performance of the music. Virtuosity is also formed by a combination of the education of playing the instrument and the present repertoire. Virtuosity necessitates, first of all, that the technical limits of the instrument should be forced and these boundaries should be continuously expanded. Tanburi Cemil Bey, has fundamentally restructured the style of the "tanbur" while he brought an innovative movement and color to other instruments such as the "kemence". Tanburi Cemil Bey's virtuosity can be found today only in his recodings. Although he was widely followed and imitated not only in the "tanbur" but also in the "kemence", lute, cello and the "yaylı tanbur", he did not leave behind written documents for coming generations that would reveal, teach and develop his new virtuosity.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1995
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1995
Keywords: Tanburi Cemil Bey; Tanburi Cemil Bey